How the brain heals emotional wounds: the functional neuroanatomy of forgiveness - Ricciardi, Emiliano; Rota, Giuseppina; Sani, Lorenzo; Gentili, Claudio; Gaglianese, Anna; Guazzelli, Mario; Pietrini, Pietro (Frontiers in Human Neuroscience, 2013)
In life, everyone goes through hurtful events caused by significant others: a deceiving friend, a betraying partner, or an unjustly blaming parent. In response to painful emotions, individuals may react with anger, hostility, and the desire for revenge. As an alternative, they may decide to forgive the wrongdoer and relinquish resentment. In the present study, we examined the brain correlates of forgiveness using functional Magnetic Resonance Imaging (fMRI). Healthy participants were induced to imagine social scenarios that described emotionally hurtful events followed by the indication to either forgive the imagined offenders, or harbor a grudge towards them. Subjects rated their imaginative skills, levels of anger, frustration and/or relief when imagining negative events as well as following forgiveness. Forgiveness was associated with positive emotional states as compared to unforgiveness. Granting forgiveness was associated with activations in a brain network involved in theory of mind, empathy and the regulation of affect through cognition, which comprised the precuneus, right inferior parietal regions and the dorsolateral prefrontal cortex. Our results uncovered the neuronal basis of reappraisal-driven forgiveness, and extend extant data on emotional regulation to the resolution of anger and resentment following negative interpersonal events.